J wave syndromes in patients with spinal and bulbar muscular atrophy: original communication - Steinmetz, Karoline; Rudic, Boris; Borggrefe, Martin; Müller, Kathrin; Siebert, Reiner; Rottbauer, Wolfgang; Ludolph, Albert C.; Buckert, Dominik; Rosenbohm, Angela (Journal of neurology, 2022)
Males with X-linked recessive spinobulbar muscular atrophy (SBMA) are reported to die suddenly and a Brugada electrocardiography (ECG) pattern may be present. A hallmark of this pattern is the presence of ST segment elevations in right precordial leads associated with an increased risk of sudden cardiac death.
Gesehen am 19.12.2023